2016
DOI: 10.1108/bfj-03-2016-0127
|View full text |Cite
|
Sign up to set email alerts
|

“Quality does not sell itself”

Abstract: Purpose Food quality is a multi-dimensional concept comprising both objective and subjective components. Quality as defined from an industry perspective usually relies on different instrumental assessment and on ratings of “experts” which may not necessarily align with consumers’ perception of quality. The purpose of this paper is to deal with consumers perceptions of intrinsic quality in coffee from a sensory scientific and behavioral economic perspective. Design/methodology/approach In a blind taste test (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…The instruments may be sophisticated, sensory evaluation depends to a great extent on the practitioner's physiological and psychological characteristics (Zhang & Chen, 1997 On the first and second day of the study, the data indicated that the quality measured and perceived by Q-Graders did not present statistical difference between these professionals. According to Giacalone, Fosgaard, Steen, and Münchow (2016), taste preferences are learned mainly after repeated exposure. Q-Graders, when trained and familiar with a certain quality standard, will tend to the right ones.…”
Section: Discussionmentioning
confidence: 99%
“…The instruments may be sophisticated, sensory evaluation depends to a great extent on the practitioner's physiological and psychological characteristics (Zhang & Chen, 1997 On the first and second day of the study, the data indicated that the quality measured and perceived by Q-Graders did not present statistical difference between these professionals. According to Giacalone, Fosgaard, Steen, and Münchow (2016), taste preferences are learned mainly after repeated exposure. Q-Graders, when trained and familiar with a certain quality standard, will tend to the right ones.…”
Section: Discussionmentioning
confidence: 99%
“…With increasing demand worldwide, particularly in the specialty coffee segment, scientific sensory evaluation of coffee is increasingly sought after to understand and meet consumer demands [3,4]. The sensory quality of coffee is a function of all the links in the coffee production chain-plant genetics, terroir, transportation, storage, roasting, grinding, brewing-which, together with social, psychological, and situational factors, determine the final consumer experience [5][6][7][8][9][10][11]. A clear picture of how each link, as well as the subprocesses in each link, modulates the flavour of the coffee is necessary in order to inform product development and quality control, that is to have the opportunity to create high-quality products that consistently give a satisfying consumer experience [5,10].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, roasting time was negatively associated both with respect to "balance" and "clean cup", although for "balance", only the effect of development time was significant. Results for these two attributes should be interpreted with caution in light of their semi-hedonic nature; in particular, because expert scores may not necessarily correlate with consumer preferences [8] and also because in-depth analyses revealed a poor agreement between experts for these attributes [39]. Table 5.…”
mentioning
confidence: 99%
“…Quality Assurance and Safety of Crops & Foods, 2020;12 (2): 24-39 Every product or service has two types of quality, which are objective and subjective quality. Objective quality refers to product-related characteristics that can be measured using technical instruments (Giacalone et al, 2016). Subjective quality, on the other hand, is consumers' perceptions (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…A product would sell if consumers perceived its quality to be high. Perception or subjective quality has more weight than objective quality (Giacalone et al, 2016). However, in the drug and functional food industry, this inequality was reduced by regulations that control the objective quality of functional foods.…”
Section: Introductionmentioning
confidence: 99%